2019
DOI: 10.1136/bmjopen-2018-027441
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-year visual outcomes from the Moorfields age-related macular degeneration database: a retrospective cohort study and an open science resource

Abstract: ObjectivesTo analyse treatment outcomes and share clinical data from a large, single-centre, well-curated database (8174 eyes/6664 patients with 120 756 single entries) of patients with neovascular age-related macular degeneration (AMD) treated with anti-vascular endothelial growth factor (VEGF). By making our depersonalised raw data openly available, we aim to stimulate further research in AMD, as well as set a precedent for future work in this area.SettingRetrospective, comparative, non-randomised electronic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…64,65 Three recent publications from the same institution had slightly different visual outcomes. 26,27,41 Some of this relates to the time-point when eyes were included, consistent with a national trend for better outcomes over time.…”
Section: Inter-centre and Intra-centre Variation In Visual Outcomesmentioning
confidence: 73%
“…64,65 Three recent publications from the same institution had slightly different visual outcomes. 26,27,41 Some of this relates to the time-point when eyes were included, consistent with a national trend for better outcomes over time.…”
Section: Inter-centre and Intra-centre Variation In Visual Outcomesmentioning
confidence: 73%
“…Overall mean number of injections received was 52.2 over a period of 10 years. Previous studies on long-term outcomes at 1,2 5 and 7 years have all shown the reduced effectiveness of anti-VEGF agents in clinical practice and most reports have attributed these results to the reduced number of injections over time [5,6,[10][11][12][13]. Qin et al in their study on long term outcomes of exudative AMD treatment have attributed the variable results to the differences in frequency and regularity of anti-VEGF treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…As data from real-world studies suggest that patients receive fewer injections than those studied in clinical trials, the benefit seen from a TREX regime likely comes from its proactive nature, as a higher number of injections are also associated with better visual outcomes. 28 , 37 , 50 , 118 …”
Section: Anatomic Factorsmentioning
confidence: 99%